African researchers and decision-makers : building synergy for development - Ndiaye, Abdoulaye (Council for the Development of Social Sciences Research in Africa, 2009)
For the International Development Research Centre (IDRC) and its partners, the link between research and policy is of paramount importance in their goal to improve social, economic and environmental conditions in developing countries. The nature of the collaboration between researchers and decision-makers, however, is complex, multifaceted and often difficult to implement. Moreover, research is very often designed and carried out without regard for its potential users or beneficiaries. How should research agendas be developed? What is the role of the private sector in developing research? Which actors are involved in knowledge production and utilization? How can the dialogue between researchers and decision-makers be improved? This short and accessible book records the reflections, opinions and recommendations which emerged from six national workshops organised between 2004 and 2007 in West and Central Africa on the synergy between researchers and decision-makers. Abdoulaye Ndiaye is a Senegalese expert and international consultant in development. He edited this book as a member and on behalf of the IDRC Council of Regional Advisors for West and Central Africa which organized the series of workshops throughout the sub-region.